THE CHALLENGE OF IMPLEMENTING ONLINE INTERPROFESSIONAL EDUCATION FOR UNDERGRADUATE STUDENTS: A LITERATURE REVIEW - Rilani Riskiyana (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2021)
Background: Interprofessional education (IPE) is undergoing vast development recently. Online learning has been proven to help overcoming the barriers that were commonly found in traditional IPE. However, the management of online learning in IPE is not well understood. The study identified challenges in online learning in IPE as well as recommendations for better program implementation. Methods: A literature review was performed using several keywords including “online learning”, “blended learning”, “interprofessional education”, “challenges”, and “obstacles”. The databases included EBSCOHost, ProQuest, Google Scholar, and Sciencedirect. A narrative analysis was performed to meet the review objective. Results: The identified challenges in establishing online learning for IPE were categorized according to each phase, i.e. planning and implementation. Seven categories of challenge were highlighted. The recommendations to overcome each challenge were also discussed for better implementation in the future. Conclusion: Understanding the possible challenge in each phase of developing online learning for IPE could minimize the potential disruption in achieving the learning objective. Gaining support as well as faculty trainings are crucial to ensure the program sustainability